Heat tolerance in Pantaneiro horses subjected to different exercise regimes - Santos, Sandra Aparecida; da Silva, Gianni Aguiar [UNESP]; de Rezende, Adalgiza Souza Carneiro; de Faria, Danielle Assis; Soriano, Balbina Maria; McManus, Concepta (FapUNIFESP (SciELO), 2022)
The objective of this work was to determine how different types of gait affect the physiological and thermographic responses of Pantaneiro horses (Equus ferus caballus) subjected to field conditions under high environmental temperatures. Ten horses were evaluated in a double 5x5 Latin square experimental design, with five gait types: walk, trot, extended trot, gallop, and extended gallop. The following physiological measures were determined immediately after exercise: heart and respiratory rates, blood lactate content, and rectal temperature. Body surface temperatures were evaluated using an infrared camera. The walk, trot, and extended trot were the most adequate gaits for Pantaneiro horses to maintain thermoregulation within the physiological norms under conditions with a high air temperature. The temperatures obtained in the eye and elbow regions show the best predictive capacity for physiological parameters.
Tolerância ao calor em cavalos Pantaneiros sob diferentes regimes de exercício
Keywords: animal welfare; body temperature; Equus ferus caballus; gait; lactate; thermal balance; thermal stress